Perbandingan Efek Antara Mobilization of the Nervous as System Active Exercise Terhadap Perubahan Nyeri dan Fleksibilitas Penderita Low Back Pain - Djohan Aras (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Low Back Pain (LBP) is a disturbance attacked the lower area of the back due to various either musculoskeletal problems or incorrect mobilization. LBP can produce pain sensation and diminishing lumbal flexibility so that it disturbs patient’s activity. Mobilization of the Nervous as System (MONAS) and Active Exercise are training methods used to decrease pain and increase flexibility in LPB patients. This research aimed to identify The Comparison between MONAS and Active Exercise on Changes of Pain and Flexibility in Patients Suffering from Low Back Pain (LBP). The recent study was an experimental study with pre test-post test two group design. The sampling was conducted by using purposive sampling method. The number of samples was 22 samples divided into 2 groups namely groups of MONAS and Active Exercise. Each group consisted of 11 respondents. The measurement tools used were Visual Analogue Scale (VAS) to measure the pain level and Modified Schober Test (MST) to assess the flexibility. This research used paired t-test as test of effect while independent sample t-test was used as comparative test. Analysis of paired sample t-test showed that there was changes in pain and flexibility levels in LBP patients after administration of either MONAS (p value = 0.000) or Active Exercise (p value = 0.000). Independent sample t-test gave p value = 0.658 and 0.729 for pain and flexibility, respectively. As conclusion, there was no significant difference between MONAS and Active Exercise either on pain or flexibility levels